Digital Campaign Performance Analysis: A Case Study of TikTok Channel Addition and Influencer Utilization for Cafes in Malang City - Mourryn Galuh Erawati; M. Syauqi Haris; Ahsanun N. Khudori (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The digital revolution has transformed how brands connect with their audiences, making social media platforms essential tools for building strong relationships. Instagram and TikTok play crucial roles in boosting user engagement, particularly among active users who have integrated these platforms into their daily lives for both information seeking and entertainment purposes. Our study examines how digital strategies can drive engagement rate improvements across social media channels, focusing on creative content usage and channel selection that matches target audience characteristics. We employed quantitative methodology through direct observation of interaction indicators including views, likes, comments, shares, and saves. Performance analysis compared social media metrics before and after digital strategy implementation. As a case study, we analyzed Kogu Cafe, a culinary business that began implementing visual content strategies, expanding distribution channels through TikTok, and establishing collaborations with local influencers. Results demonstrate substantial engagement rate increases. On Instagram, user involvement grew from approximately 1.5% to over 5% within three months. Meanwhile, TikTok achieved peak performance in April with an engagement rate of 5.42%. Influencer collaborations with Khuril and Bibilcu also generated positive impacts, producing engagement levels of 7.20% and 5.79% respectively. These findings indicate that well-structured digital strategies adapted to audience behavior patterns can deliver measurable impacts on social media performance.